2020
DOI: 10.4204/eptcs.329.2
|View full text |Cite
|
Sign up to set email alerts
|

Towards Compositional Verification for Modular Robotic Systems

Abstract: Software engineering of modular robotic systems is a challenging task, however, verifying that the developed components all behave as they should individually and as a whole presents its own unique set of challenges. In particular, distinct components in a modular robotic system often require different verification techniques to ensure that they behave as expected. Ensuring whole system consistency when individual components are verified using a variety of techniques and formalisms is difficult. This paper dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…This work uses distinct verification methods for specific components but does explicitly link the verification artifacts produced. Recent work proposes first-order logic to unify heterogeneous formal methods via a compositional approach but this work currently lacks tool support [7].…”
Section: Related Workmentioning
confidence: 99%
“…This work uses distinct verification methods for specific components but does explicitly link the verification artifacts produced. Recent work proposes first-order logic to unify heterogeneous formal methods via a compositional approach but this work currently lacks tool support [7].…”
Section: Related Workmentioning
confidence: 99%
“…Related, a recent survey of formal specification and verification techniques for autonomous robotic systems has revealed that, although there are many tools and techniques available, improvements are still required for their successful deployment in large, complex and autonomous systems (Farrell et al, 2018;Luckcuck et al, 2019). Given modular robot architectures composed of distinct subsystems, different types of verification can potentially be used for different components, as described in (Farrell et al, 2019b;Cardoso et al, 2020a;Cardoso et al, 2020b), as some verification techniques may be more appropriate than others for certain subsystems. Our work also uses multiple distinct verification techniques (Dafny and ROSMonitoring) to verify different components/aspects of the system.…”
Section: Related Workmentioning
confidence: 99%
“…• the initial presentation of the contract calculus in [11], which we significantly update; and, • our application of heterogeneous verification approaches to a simulation of the Mars Curiosity rover [12], which we also update with additional steps.…”
Section: Can We Use a Compositional And Heterogeneous Approach To Ver...mentioning
confidence: 99%